2018
DOI: 10.1101/379545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual grouping in the cocktail party: contributions of voice-feature continuity

Abstract: 23

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Similar to several of our previous studies [34][35][36], we followed an iterative model-fitting procedure: Starting with the minimal model that only included the subjectspecific random intercepts, we first added fixed-and then random-effects terms in a step-wise fashion. Fixedeffect terms were added in the order of their clinical importance (i.e., diagnosis, vestibular symptoms, surface, eyes, and interactions between these factors).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to several of our previous studies [34][35][36], we followed an iterative model-fitting procedure: Starting with the minimal model that only included the subjectspecific random intercepts, we first added fixed-and then random-effects terms in a step-wise fashion. Fixedeffect terms were added in the order of their clinical importance (i.e., diagnosis, vestibular symptoms, surface, eyes, and interactions between these factors).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that in the context of naturally-varying voices, using such spectral representations as acoustic measures is preferable to other measures that have frequently been used in voice research, such as the mean F0 and/or measures derived from formants, such as vocal tract length (Baumann & Belin, 2010;Gaudrain, Li, Ban & Patterson., 2009;Kreitewolf, Mathias, Trapeau, Obleser & Schönwiesner, 2018;Lavner et al, 2000; see Mathias & von Kriegstein, 2014, for a review). First, the spectral representations we describe are richer signals that include -but are not restricted to -F0 and formant-related acoustic information within the same measure.…”
Section: Experiments 1: Voice Identity Discriminationmentioning
confidence: 99%
“…This phenomenon is known as the cocktail party effect (CPE) and can be difficult for machines to imitate [1], [2], [3], [4]. The CPE has been the subject of many studies [5], [6], [7], [8], [9], [10], [11]. Researchers in the fields of psychophysics and neuroscience have discovered that besides binaural spatial cues, monaural cues also play an important role in CPE tasks [7], [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, evidence suggests that listeners can rely solely on monaural cues to recognize a target speech in the presence of a masking speech. Past experiments showed that differences in the spectral envelope and base frequency-also referred to as the fundamental frequency (F0)-between concurrent speech streams are the two most influential monaural cues [7], [8], [9], [13]. F0 is determined by vocal cord vibration while the configuration of the vocal tract determines the spectral envelope [7], [14].…”
Section: Introductionmentioning
confidence: 99%